Effectiveness of EU Law and Policy on Vertical Restraints at Protecting Competition - Raad, Puya (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
In reviewing European competition law one might raise doubts about EU competition policy to the extent that it is questionable who the law is protecting in practice; consumers and weaker competitors or the status quo of the ‘big fishes’ and their well-performing distribution, legally justified under current law and the ECJ´s approach to American interpretation of competition protection. In the following paper these doubts are discussed in the context of the relevant ECJ cases and opinions in the literature. There is an attempt to answer the question of whether and in which circumstances EU law can be effective in protecting competition.
Keywords: Unia Europejska; prawo konkurencji